PENGARUH MEDIA SOSIAL DAN PENDIDIKAN ETIKA BISNIS TERHADAP PERSEPSI MAHASISWA AKUNTANSI STIE CENDEKIA BOJONEGORO TENTANG PERILAKU KONSUMTIF - Nadila Aprilia Ramawati; Sisca Noor Amanah; Tri Nur Lailita; Wiji Mahareni; Yella Dewi Anggraini (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
This study analyzes the influence of social media and business ethics education on the perception of accounting students of STIE Cendekia Bojonegoro regarding consumptive behavior. The method used was a quantitative survey with data collection through questionnaires, involving 40 respondents who were selected purposively. The results showed that social media had a significant influence on students' consumptive behavior (regression coefficient 0.531, p<0.05), while business ethics education also had a significant positive influence on consumptive behavior (regression coefficient 0.502, p<0.05). Overall, social media encourages consumptive behavior, while business ethics education helps shape more responsible consumption patterns. This study emphasizes the importance of integrating ethical values in education to manage the negative impact of social media on student consumption behavior. Social media has a significant influence on students' consumptive behavior, Business ethics education also has a positive effect on consumptive behavior by providing a moral framework for more responsible consumption. Both variables simultaneously affect students' perception of consumption.